2009
DOI: 10.1042/bst0370133
|View full text |Cite
|
Sign up to set email alerts
|

Small RNAs of the halophilic archaeon Haloferax volcanii

Abstract: In recent years, sRNAs (small non-coding RNAs) have been found to be abundant in eukaryotes and bacteria and have been recognized as a novel class of gene expression regulators. In contrast, much less is known about sRNAs in archaea, except for snoRNAs (small nucleolar RNAs) that are involved in the modification of bases in stable RNAs. Therefore bioinformatic and experimental RNomics approaches were undertaken to search for the presence of sRNAs in the model archaeon Haloferax volcanii, resulting in more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 30 publications
0
23
0
3
Order By: Relevance
“…The red/green ratio denotes the average signal strengths of cDNAs generated from RNA co-purified with the FLAG-Lsm protein divided by the average signal strengths of a negative control cDNA generated from RNA purified from cultures only expressing the FLAG peptide. RNAs termed "sRNA" were previously identified as sRNAs in Haloferax (37,38). RNAs termed "H" and "p" had been predicted as sRNAs using bioinformatic approaches.…”
Section: Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…The red/green ratio denotes the average signal strengths of cDNAs generated from RNA co-purified with the FLAG-Lsm protein divided by the average signal strengths of a negative control cDNA generated from RNA purified from cultures only expressing the FLAG peptide. RNAs termed "sRNA" were previously identified as sRNAs in Haloferax (37,38). RNAs termed "H" and "p" had been predicted as sRNAs using bioinformatic approaches.…”
Section: Proteinmentioning
confidence: 99%
“…Interestingly, Methanocaldococcus jannaschii lacks a classical Lsm gene (9,36) Recently, it has been shown that H. volcanii also has an sRNA population potentially involved in gene expression regulation (37,38). To investigate whether the Haloferax Lsm is involved in sRNA regulation and to clarify its biological function, we generated a deletion strain for Lsm and analyzed the in vivo and in vitro function of this protein.…”
mentioning
confidence: 99%
“…They led to the elucidation of sRNAs in all tested archaeal species, i.e., Archaeoglobus fulgidus, 27 Sulfolobus solfataricus, 28 Methanosarcina mazei 29 and H. volcanii. 30,31 In summary, the picture emerged that the presence of sRNAs is widespread in archaea and that the number is comparable to the number of sRNAs in bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, RNomics revealed the presence of additional sRNAs in two archaeal organisms: Sulfolobus solfataricus and Archaeoglobus fulgidus [11,12]. Since that time, sRNAs have been identified in several archaeal species [13][14][15][16][17][18][19][20][21]. In addition to the already identified snoRNAs, cis-encoded antisense RNAs and trans-encoded sRNAs were identified (for a review, see [22]).…”
mentioning
confidence: 99%